High cadmium pollution from sediments in a eutrophic lake caused by dissolved organic matter complexation and reduction of manganese oxide. (15th February 2021) - Chen, Musong; Ding, Shiming; Li, Cai; Tang, Yazhou; Fan, Xianfang; Xu, Huacheng; Tsang, Daniel C.W.; Zhang, Chaosheng
Highlights: A yearlong field monitoring showed large variation in Cd mobility in sediments. Increased sediment Cd pollution in February and March resulted from Mn redox cycle. A sudden outbreak of Cd pollution in May and June resulted from DOM complexation. Combined stabilization mechanisms led to low Cd pollution in other months. Abstract: Eutrophication and metal pollution are global environmental problems. The risk of metal pollution is high in the eutrophic lakes because of high mobility of metal in sediments. However, the mechanism of cadmium (Cd) mobility in sediments is still unclear. Here we study the mobilization of Cd in sediments from the eutrophic Lake Taihu via monthly field monitoring of mobile Cd using diffusive gradient in thin films (DGT) and high resolution dialysis (HR-Peeper) techniques. We found a high mobility of Cd in sediments in February and March, resulting from reductive dissolution of Mn oxide mediation by high microbial activities, as shown by the similarities in distribution patterns of DGT-labile Cd and Mn. A two orders of magnitude increase in dissolved Cd concentrations (about 28 μg L −1 ) was observed in May and June, with dissolved Cd concentrations in overlying water about 110 times higher than the criteria continuous concentration set by Environmental Protection Agency. Hourly changes were found to coincide and correlate between dissolved Cd and dissolved organic matter (DOM) under simulated anaerobic conditions, strongly suggesting that the sudden outbreak of Cd pollution observed in the field resulted from the complexation of DOM with Cd in sediments. This was further supported by the NICA-Donnan model that more than 71% of dissolved Cd in the pore water in May and June was present as Cd-DOM complexes. Three components of DOM including humic-, tryptophan-, and tyrosine-like components in the sediments in June was identified using the fluorescence excitation emission matrix-parallel factor analysis. We found that Cd was stable complexed with tyrosine-like component. The Fourier transform infrared and two-dimensional correlation spectroscopy further revealed that Cd was bound to phenolic OH, alkene CC, alcoholic CO, aromatic CH, and alkene CH groups. Our study effectively promotes the understanding of Cd mobilization in sediments and highlights the risk of sudden Cd pollution events in the eutrophic lakes. Graphical abstract: Image, graphical abstract